41.1k views
3 votes
0.6 (h + 10) = 9
Help please

1 Answer

4 votes

Answer:

h=5

Explanation:

Simplifying

0.6(h + 10) = 9

Reorder the terms:

0.6(10 + h) = 9

(10 * 0.6 + h * 0.6) = 9

(6 + 0.6h) = 9

Solving

6 + 0.6h = 9

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-6' to each side of the equation.

6 + -6 + 0.6h = 9 + -6

Combine like terms: 6 + -6 = 0

0 + 0.6h = 9 + -6

0.6h = 9 + -6

Combine like terms: 9 + -6 = 3

0.6h = 3

Divide each side by '0.6'.

h = 5

Simplifying

h = 5

User Arjun Arora
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.